A double conundrum: concurrent presentation of Hashimoto's thyroiditis and ulcerative colitis. (22nd April 2016) - Singh, Gurpreet; Brien, Susie; Taylor, Ellen
Abstract : We describe a case of a 31-year-old man who presented with a 3-day history of crampy abdominal pain, anorexia, malaise and diarrhoea of increasing frequency, with the passage of both mucus and haematochezia. The patient's biochemical investigations revealed hyponatraemia, hypothyroidism and elevated inflammatory markers. The patient underwent an ultrasound and fine-needle aspiration of the thyroid and was diagnosed as having Hashimoto's thyroiditis. He was started on thyroxine and fluid was restricted. He was also investigated for alternative causes of hyponatraemia. With improvement in his hyponatraemia, the patient underwent a colonoscopy with biopsies confirming a concurrent diagnosis of ulcerative colitis. He was started on mesalazine and prednisolone and discharged from hospital. He suffered a flare shortly after discharge and was readmitted to hospital. He was again discharged, on a higher dose of prednisolone, with outpatient follow-up at our hospital's gastroenterology clinic.